The Relationship between Family Participation and the Growth of Pre-School Children During the Covid-19 Pandemic in the Working Area of the UPT Puskesmas Kampung Bugis - Maria Goreti Timung; Andi Lis Arming; Nilam Noorma (PT FORMOSA CENDEKIA GLOBAL, 2023)
The problem of growth along with the problem of child nutrition is a public health problem that has a multifactorial impact on the quality of life of children as the next generation of the nation. This study aims to determine the relationship between family participation and the growth of pre-school children. Using a correlational quantitative design approach cross sectional Sommers'd test on a sample of 59 by purposive sampling. Families as respondents have heads of families with high school education (n=37; 62.7%), nuclear family (n=53; 89.8%), as private workers (n=38; 64.4%), and have one person pre-school age children (n=25; 44.1%). The majority of family participation was good (n = 42; 71.2%) and the growth of the majority of pre-school children was normal (n = 29; 49.2%). There is a strong relationship between family participation and the growth of pre-school children in the working area of ​​the UPT Puskesmas Kampung Bugis (sig 0.000; value 0.651).